The Transition to Carbon Capture and Storage Technologies - Rolf Golombek; Mads Greaker; Snorre Kverndokk; Lin Ma (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We model the value chain of Carbon Capture, transport and Storage (CCS) by focusing on the decisions taking by actors involved in either capture, transport or storage of CO2. Plants emitting CO2 are located along a Salop circle. If these invest in carbon capture facilities, the captured CO2 is transported to terminals, which again transport the received amount of CO2 to a storage site. We study different market structures, all suffering from market imperfections such as network effects, market power and economics of scale in addition to the environmental externality from emissions. Thus, to ensure socially optimal CCS investments, the government must use more than one policy instrument. A numerical specification of the model finds that the actually observed CCS investments are much lower than what is socially optimal simply because the price of CO2 emissions has been far too low. If the carbon tax is set equal to the social cost of carbon and is sufficiently high to justify CCS investments, but the government does not use other instruments to correct for the other market imperfections, CCS investments differ significantly between the alternative market structures. In particular, investment in terminals may be too high, while investment in capture facilities could still be too low.
Keywords: H23; L13; L51; Q35; Q38; 330; carbon capture and storage; indirect network effects; Salop circle; carbon tax; market imperfections; tipping points